2021
DOI: 10.1111/are.15478
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of dietaryMoringa oleiferaon hemato‐biochemical and oxidative stress of lead nitrate intoxicated Nile tilapia,Oreochromis niloticus

Abstract: The aquatic ecosystems are the final destination for almost all anthropogenic discharges as well as industrial effluents (Eroglu et al., 2015). Metals are neither biodegradable nor eliminated in the ecosystem. Hence their presence at the super optimal level can threaten aquatic biota. In polluted water, the concentration of these metals can be many folds of their natural level at sites where excess amounts of anthropogenic input exist (Heath, 2018;Mance & Mance, 1987).Since fish occupy the top of the aquatic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Abdel‐Tawwab and Hamed (2020), reported that Psidium guajava reduced the negative effects of cypermethrin. Kiran Kumar et al (2021), found that Moringa oleifera had a protective effect against nitrate intoxication in Nile tilapia. Similar to this study, it has been shown that herbal and chitosan‐derived applications will provide a protective effect and survival of fish and protection against pollutants such as heavy metals and carbofuran (Hamed & Abdel‐Tawwab, 2021; Hamed & Osman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Abdel‐Tawwab and Hamed (2020), reported that Psidium guajava reduced the negative effects of cypermethrin. Kiran Kumar et al (2021), found that Moringa oleifera had a protective effect against nitrate intoxication in Nile tilapia. Similar to this study, it has been shown that herbal and chitosan‐derived applications will provide a protective effect and survival of fish and protection against pollutants such as heavy metals and carbofuran (Hamed & Abdel‐Tawwab, 2021; Hamed & Osman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The present results were comparable to those of Chandurvelan et al [ 14 ] and Hu et al [ 56 ], while Perna canaliculus was tested through exposure to several trace elements, and Mytilus coruscus was treated with toxic nanoparticles, respectively, which eventually resulted in poor physiological conditions and growth performance. Reduced growth metrics have also been consistently observed in several fish species owing to lead toxicity [ 10 , 18 , 57 ]. In contrast, the effect of heavy metals on growth was insignificant when Lampsilis siliquoidea was exposed to copper [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that aquatic species pick up this kind of toxic metal following the concentrations present in the neighboring environment [ 4 , 17 ]. The biological equilibrium becomes highly threatened if the concentration of Pb grows beyond the tolerance limit in an aquatic ecosystem, ultimately resulting in the degradation of the entire ecosystem [ 14 , 18 ]. Thus, the higher the heavy metal discharge into the water, the greater the accumulation of heavy metals in the living tissues and sediments [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Pb causes the accumulation of heavy metals, histopathology, and neurotoxicity in fish (Lee et al, 2019 ; Shahjahan et al, 2022 ). Lead accumulation can also cause oxidative stress in aquatic organisms and damage the antioxidant function of the body (Guo et al, 2021 ; Kumar et al, 2021 ). Therefore, several antioxidant markers, such as antioxidant enzymes (GST and CAT) and glutathione (GSH), are often used to evaluate the toxic effects of Pb-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%